Phases in the junior-to-senior transition of Swedish ice hockey players: From a conceptual framework to an empirical model - Stambulova, N. B.; Pehrson, S.; Olsson, C. (International Journal of Sports Science & Coaching, 2017)
The purpose of this study was to explore a temporal structure (i.e. sequence of phases and relevant psychological content) of the junior-to-senior transition in Swedish ice hockey players. The study was a qualitative exploration of the junior-to-senior transition process designed in three steps. First, the athletic career transition model coupled with a holistic developmental approach and analysis of the Swedish ice hockey context were used to create a conceptual four-phase (preparation, orientation, adaptation and stabilization) junior-to-senior transition framework and interview guides. Second, seven active semi-professional ice hockey players were interviewed about their junior-to-senior transition experiences and asked for their feedback on the conceptual framework. Finally, based on the empirical data and the participants` feedback, the conceptual framework was transformed into an empirical model of the junior-to-senior transition. In the empirical model `Phases in the junior-to-senior transition of Swedish ice hockey players`, the authors provided a summary of the players` transition experiences (i.e. perceived demands, resources, barriers, coping strategies and outcomes) within each of the four (i.e. the preparation, the orientation, the adaptation and the stabilization) junior-to-senior transition phases. Further, the authors discussed the empirical model in relation to theoretical frameworks and previous research and also provided methodology-, future research- and practice-oriented reflections addressed to researchers, coaches and sport psychology practitioners FROM AUTHOR